KAJIAN KEMAMPUAN CAMPURAN ASPAL-BETON (AC-BC) DENGAN ASBUTON CAIR YANG DIISI DENGAN SERPIHAN HDPE (HIGH DENSITY POLYETHYLENE) - Okma Yendri; Wahyu Septiandi (Jurnal Teknik Gradien, 2023)
One of the things that can damage the floor is gallon water bottles, milk bottles, shampoo bottles, detergent bottles, and other thick plastics made from organic compounds and made from high-density polyethylene (HDPE) plastic. We see an opportunity to utilize the substantial amount of plastic waste as an additional material produced by hot mixing in a flexible processing structure. lasto AC-WC mixture to determine the optimal amount of bitumen in the AC-WC mixture containing HDPE plastic additive and the AC-WC mixture containing HDPE plastic additive. An empirical approach was used in this study to add the VFB value of high density polyethylene (HDPE) plastic to the number of samples that needed to be tested to get the best bitumen content (KAO). 65 percent of the minimum requirements have been met by the VFB value. The stability value of Marshall Kao is also higher when HDPE plastic is used, with deviations of 0.50%, 1.00%, and 1.50%, respectively. The flow value meets the minimum requirement of 2 mm, despite the fact that the melting value (flow value) tends to decrease. In contrast, Kao increased the value of flexibility (MQ) by 1.00% for the 0.50n HDPE plastic mix variation, and the 1.50a variation saw a significant increase. The ideal amount of asphalt (KAO) is 5.70 percent. AC-coated asphalt concrete Gross Heavy WC, Ruston Asphalt Concrete Mix Design Result - Mounted Course uses high density polyethylene (HDPE) in the asphalt mixture at 5.70%, 0.50%, 1.00%, and 1.50% for each variation of HDPE plastic mix.